The Use of Problem-Solving Therapy for Primary Care to Enhance Complex Decision-Making in Healthy Community-Dwelling Older Adults - Nguyen, Christopher M.; Chen, Kuan-Hua; Denburg, Natalie L. (Frontiers in Psychology, 2018)
Some older adults who are cognitively healthy have been found to make poor decisions. This phenomenon is based on a body of literature suggesting of a disproportionate deterioration of the frontal lobes during aging that contributes to a decline in executive functioning abilities among some older adults. The purpose of this study was to investigate whether decision-making performance in older adults can be enhanced by a psychoeducational intervention. Twenty cognitively and emotionally intact persons aged 65 years and older were recruited and randomized into two conditions: psychoeducational condition (Problem-Solving Therapy for Primary Care [PST-PC]) and no-treatment Control group. Participants in the psychoeducational condition each received four 45-minute sessions of PST-PC across a two-week period. The Iowa Gambling Task was administered as the outcome measure to the treatment group, while participants in the Control group completed the IGT without intervention. A significant interaction effect was observed between group status and the trajectory of score differences across trials on the IGT. Particularly, as the task progressed to the last 20% of trials, participants in the PST-PC group significantly outperformed participants in the Control group in terms of making more advantageous decisions. These findings demonstrated that a four-session problem-solving therapy can reinforce aspects of executive functioning (that may have declined as a part of healthy aging), thereby enhancing complex decision making in healthy older adults.